2011
DOI: 10.3102/0013189x11419042
|View full text |Cite
|
Sign up to set email alerts
|

Stayers and Leavers

Abstract: Research on teacher development reports significant early-career increases in teacher effectiveness, but the extent to which this is attributable to the development of teachers who persist or to the attrition of less effective teachers is unclear. In this study of novice teachers in North Carolina public schools, the authors investigated the development of teachers' effectiveness during their first five years in the classroom and contrasted the effectiveness of teachers who stayed with that of those who left. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(31 citation statements)
references
References 26 publications
2
28
1
Order By: Relevance
“…This finding is in line with the research of Henry, Bastian, and Fortner (2011) who found that average beginning American teachers' effectiveness increases during the first three years of teaching. Over time, the developmental level of activating learning, adaptation, and teaching learning strategy never reached that of learning climate, clarity of instruction, and classroom management.…”
Section: Does Student Perception Of Beginning Teachers' Teaching Qualsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in line with the research of Henry, Bastian, and Fortner (2011) who found that average beginning American teachers' effectiveness increases during the first three years of teaching. Over time, the developmental level of activating learning, adaptation, and teaching learning strategy never reached that of learning climate, clarity of instruction, and classroom management.…”
Section: Does Student Perception Of Beginning Teachers' Teaching Qualsupporting
confidence: 93%
“…Our finding is in line with past research revealing that the induction program was related to increased reflection, improved collegiality, openness and communication, greater teacher autonomy, self-growth, and personal efficacy among English beginning teachers (Smethem & Adey, 2005). The developmental trend of beginning teachers in the non-induction group, on the other hand, is more in line with Henry et al (2011) indicating that teaching quality will tend to flatten after three years of professional practice. The induction program seems to be powerful in mitigating this plateauing trend during the early career.…”
Section: Does Student Perception Of Beginning Teachers' Teaching Qualsupporting
confidence: 92%
“…In fact, levels of attrition could be seen as positive or negative depending on which teachers are staying and which teachers are leaving. It is also important to consider the factors that may influence teacher decisions to stay, or to leave, the profession (Henry, Bastian, & Fortner, 2011;OECD, 2005a). At this point in time, it appears that there is no evidence either way to link teacher attrition with student performance.…”
Section: Supporting Teachers Once They Are In the Systemmentioning
confidence: 99%
“…Evidence concerning the impact of teacher credentials indicates that, on average, experience and certification status are often significantly associated with student achievement gains for early-career teachers (Boyd et al 2006;Vigdor 2007, 2010;Henry, Bastian, and Fortner 2011). Results concerning National Board Certification and teacher test scores are mixed across research settings, but in North Carolina, both credentials generally signal teacher quality Vigdor 2007, 2010;Goldhaber 2007;Goldhaber and Anthony 2007;Buddin and Zamarro 2009).…”
Section: Teacher Qualitymentioning
confidence: 91%